2012
DOI: 10.1016/j.phrs.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged signalling and trafficking of the bradykinin B2 receptor stimulated with the amphibian peptide maximakinin: Insight into the endosomal inactivation of kinins

Abstract: Maximakinin, a 19-residue peptide from the amphibian Bombina maxima, incorporates the full sequence of bradykinin (BK) at its C-terminus with a hydrophilic 10-residue N-terminal Maximakinin is the first known natural kinin sequence that elicits a prolonged cellular signalling, thus suggesting a possible basis for a venomous action and a naturally selected one for the design of B 2 R-transported biotechnological cargoes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 29 publications
6
30
0
Order By: Relevance
“…The recycling of B 2 R-GFP is conveniently assessed 3 h after stimulation with BK, a fragile peptide that is rapidly cleared by different pathways in both the serum-containing culture medium and in endosomes [5] (Fig. 6, top …”
Section: Effect Of Cytochalasin D On the Recycling Processmentioning
confidence: 99%
See 2 more Smart Citations
“…The recycling of B 2 R-GFP is conveniently assessed 3 h after stimulation with BK, a fragile peptide that is rapidly cleared by different pathways in both the serum-containing culture medium and in endosomes [5] (Fig. 6, top …”
Section: Effect Of Cytochalasin D On the Recycling Processmentioning
confidence: 99%
“…Thus, the B 2 R combines with either type of non-visual -arrestins and the ligand-B 2 R--arrestin complex gets translocated into endosomes [1,2]. The fusion protein B 2 Rgreen fluorescent protein (B 2 R-GFP) -arrestins conjugated to fluorescent proteins and BK sequences that were extended with fluorophores were instrumental in modeling the BK-induced endocytosis, but also its recycling to the cell surface and the persistence of the ternary agonistreceptor--arrestin complexes in intracellular structures [3][4][5] (and literature cited herein).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest is that only the leucine residue substitution at position 8 of BK would cause such an astonishing function loss. Leucine 1 is a common substitution occurred in BRPs, compared with valine substation at position 1, it normally exhibits moderate agonistic effect of BK [26]. As the fact that Leu8-BK was reported as a BK receptor antagonist [27], we performed further experiments to examine whether RAP-L1, T6-BK and its analogue RAP-L1, T6, L8-BK could inhibit BK-induced relax on rat tail artery smooth muscle, the results revealed that, as expected, RAP-L1, T6-BK did not show BK inhibition property (Figure S1), but RAP-L1, T6, L8-BK significantly reduced BK relaxation activity on rat tail artery nearly 50% in the concentration range 10 −8 M–10 −5 M. These data suggested that although this novel BRP has a three residues -RAP- extension and leucine 1, threonine 6 substitutions, the leucine 8 still plays the essential and dominant role in reversing the BK’s effect.…”
Section: Discussionmentioning
confidence: 99%
“…Endosomal BK degradation obligatorily precedes the dissociation of β-arrestins from the B 2 R and receptor recycling to the cell surface, as shown by several inactivation-resistant B 2 R agonists that promote the persistence of this intracellular complex for at least 12 h and prolonged signaling [6,7]. Fluorophore conjugated analogs (carboxyfluorescein-or AlexaFluor-350-ε-aminocaproyl-BK) model the intracellular inactivation of the kinin, notably because the inhibitor of the proton pump V-ATPase, bafilomycin A1, prevents the time-dependent disappearance of the fluorescent peptides in endosomes of B 2 Rexpressing cells [8,9].…”
Section: Introductionmentioning
confidence: 99%